2019
DOI: 10.35473/jhhs.v1i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Efektivitas Aromaterapi Lavender Untuk Mengurangi Kecemasan Menghadapi Persalinan Pada Ibu Hamil Trimester Iii Di Wilayah Kerja Puskesmas Bergas

Abstract: Kecemasan antenatal selama kehamilan merupakan faktor resiko terjadinya depresi postpartum. Kecemasan pada trimester tiga dapat mempengaruhi proses persalinan, tumbuh kembang anak, kelahiran prematur, BBLR, partus lama dan gangguan mental. Aromaterapi adalah salah satu bagian dari pengobatan alternatif yang menggunakan bahan cairan tanaman yang mudah menguap, dapat mempengaruhi jiwa, emosi, dan fungsi kognitif serta kesehatan sesorang. Mengetahui efektivitas aromaterapi lavender untuk mengurangi kecemasan meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…J yang mengalami gangguan tidur, terjadi perubahan pola tidur ibu setelah menggunakan aromaterapi inhalasi. Hal ini mendukung gagasan bahwa pemberian inhalasi aromaterapi lavender bisa dijadikan opsi alternatif yang aman dan mudah dalam mengatasi gangguan tidur pada ibu hamil, tanpa perlu menggunakan obat tidur (Adiputri et al, 2023;Ayudia et al, 2022;Kristiningrum & Afriyani, 2019;Rhomadona & Primihastuti, 2020).…”
Section: Pembahasanunclassified
“…J yang mengalami gangguan tidur, terjadi perubahan pola tidur ibu setelah menggunakan aromaterapi inhalasi. Hal ini mendukung gagasan bahwa pemberian inhalasi aromaterapi lavender bisa dijadikan opsi alternatif yang aman dan mudah dalam mengatasi gangguan tidur pada ibu hamil, tanpa perlu menggunakan obat tidur (Adiputri et al, 2023;Ayudia et al, 2022;Kristiningrum & Afriyani, 2019;Rhomadona & Primihastuti, 2020).…”
Section: Pembahasanunclassified
“…Primigravida mothers who enter the third trimester often experience anxiety (Maki et al, 2018). A primigravida mother must understand very well what preparations are needed in the stages and process of childbirth because one of the criteria for successful delivery is psychosocial preparedness (Muthoharoh, 2018). Thus, it can be concluded that primigravida mothers, especially in the third trimester, often experience anxiety, which can cause various impacts, especially on readiness for childbirth.…”
Section: Introductionmentioning
confidence: 99%
“…Several efforts have been made to minimize the anxiety of pregnant women in Indonesia, and based on research from Miarso et al (2018), the government, especially the Ministry of Health, made a class program for pregnant women as a meeting place for multigravida and primigravida mothers. In this program, the multigravida mothers who already have the experience will share their experiences with the primigravida mothers so that knowledge and skills related to pregnancy and childbirth of the primigravida mothers and their families can be increased.…”
Section: Introductionmentioning
confidence: 99%